DE VARSOVIE Á BRUXELLES. NOTES SUR ANATOLE MÜHLSTEIN (1889–1957) ET LA BELGIQUE - Béghin, Laurent (Prace Polonistyczne, 2019)
Born in Poland in the late nineteenth century, Anatole Mühlstein (1889–1957) stayed in Belgium from 1913 to 1930. First as a student at the Université Nouvelle of Brussels and then as an employee of the Polish Embassy in Brussels, this brilliant polyglot was a cultural mediator between Poland and Belgium. This article examines different aspects of Mühlstein’s work in this field. In particular, it focuses on the role that Mühlstein played in creating “Le flambeau”, a liberal journal published in Brussels, and in determining its character in the first years of its existence.